М.НЫЗАНОВТЫҢ САТИРАЛЫҚ ГҮРРИҢЛЕРИНЕ ТАЛҚЫ - Ктайбекова, З.К. (SCIENCE and SOCIETY, 2024)
The satirical works of the famous writer M. Nizanov are analyzed in the article. The stories from the second volume of "Selected works" were selected as the object of research. Life problems in society, conflicts between people, and negative vices were criticized in the stories. Also, the character of arrogant, double-edged, unfair, unscrupulous, dishonest, rude, cowardly, lazy, careless, scheming people in the psychology of the characters is highlighted by conflict.
Keywords: satire; story; plot; humor; sarcasm; irony; skill; dialogue; character; style